Occurrence of sarcoptic mange in free-ranging vicuñas (Vicugna vicugna) of the Andean high plateau region of Argentina - Sosa, Fabiana Evangelina (2022)
Free-ranging vicuñas (Vicugna vicugna) are handled in some areas of the Andean high plateau region following an ancestral practice known as chaku, which consists in their transient capture and shearing of their fiber for commercialization. In this study, 807 vicuñas captured during 12 chaku events that took place in 2019 in the province of Jujuy, Argentina, were examined for typical mange skin lesions. Twenty-eight of the examined vicuñas presented alopecia with erythema, exudation, hyperkeratosis, and/or bleeding scarred lesions, mostly in the chest, rear and front legs, and inguinal zone. Most of the cases (82%) appeared in Laguna Cucho at 4900 masl, where 23% of the animals presented these skin reactions. Microscopic evaluation of skin scrapings revealed the presence of a great number of 0.1- to 0.4-mm-long mites of different life cycle stages, morphologically compatible with the species Sarcoptes scabiei. This etiological agent was confirmed by PCR amplification and sequencing of a cox-1 species-specific segment. Histopathological examination of skin biopsies showed extensive infiltration of the dermis with lymphocytes, neutrophils and eosinophils, hyperplasia at different stages, epidermis degeneration, and hyperkeratosis. This is the first characterization of sarcoptic mange in free-ranging vicuñas by clinical examination, mite morphology, histopathological studies, and molecular confirmation in the region. Mange hampers the welfare of vicuñas and the economy of the local communities that organize chaku events since infested vicuñas cannot be sheared. Its long-term effects are unknown but it might affect the fitness and survival of this iconic South American camelid.